2015
DOI: 10.1002/humu.22823
|View full text |Cite
|
Sign up to set email alerts
|

Choline Acetyltransferase Mutations Causing Congenital Myasthenic Syndrome: Molecular Findings and Genotype-Phenotype Correlations

Abstract: Choline acetyltransferase catalyzes the synthesis of acetylcholine at cholinergic nerves. Mutations in human CHAT cause a congenital myasthenic syndrome (CMS) due to impaired synthesis of ACh; this severe variant of the disease is frequently associated with unexpected episodes of potentially fatal apnea. The severity of this condition varies remarkably, and the molecular factors determining this variability are poorly understood. Furthermore, genotype–phenotype correlations have been difficult to establish in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…Bi‐allelic point mutations of CHAT are one of the most frequent causes of CMS (Arredondo et al, ; Byring et al, ; Engel et al, ; Kraner et al, ; Lorenzoni et al, ; Mallory et al, ; Maselli et al, ; Ohno et al, ; Schara et al, ). Molecular recessive defects in choline transporter CHT ( SLC5A7 gene) have been reported recently in six families (Bauché et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bi‐allelic point mutations of CHAT are one of the most frequent causes of CMS (Arredondo et al, ; Byring et al, ; Engel et al, ; Kraner et al, ; Lorenzoni et al, ; Mallory et al, ; Maselli et al, ; Ohno et al, ; Schara et al, ). Molecular recessive defects in choline transporter CHT ( SLC5A7 gene) have been reported recently in six families (Bauché et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The first intron of CHAT contains a small gene, SLC18A3 , which encodes vesicular ACh transporter (VAChT) (Eiden, ). Compound heterozygous (Arredondo et al, ; Lorenzoni, Scola, Kay, & Werneck, ; Ohno et al, ) or homozygous (Kraner, Laufenberg, Straßburg, Sieb, & Steinlein, ) mutations in CHAT have been identified in patients suffering congenital myasthenic syndrome (CMS) with episodic apnea (Ohno et al, ). Severity is highly variable, ranging from a lack of spontaneous breathing at birth (Engel, Shen, Selcen, & Sine, ) to mild exertion dyspnea with a myasthenic syndrome in adults, sometimes triggered by cold water (Arredondo et al, ; Maselli et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…32 In ChAT-CMS, recessive loss-of-function mutations impair the catalytic efficiency of the enzyme and decrease the release of ACh during physiologic activity. 75 Like many CMS subtypes, ChAT-CMS can exhibit striking clinical variability both between and within families. Expression studies have demonstrated that the varying severity may be explained by the degree of reduction in enzyme activity caused by the mutation.…”
Section: Chatmentioning
confidence: 99%
“…Expression studies have demonstrated that the varying severity may be explained by the degree of reduction in enzyme activity caused by the mutation. 75,76 ChAT-CMS is frequently associated with episodic apnea (EA), recurrent periods of respiratory arrest emerging in the neonatal period or during the first months of life, and often resolving with age. 77 This CMS-EA phenotype may be associated with other presynaptic CMS subtypes in which ACh synthesis and release is altered; the mechanism for these apneic events is unknown.…”
Section: Chatmentioning
confidence: 99%
“…While mutations in proteins localized both pre- and postsynaptically at neuromuscular junctions are linked to CMS (Engel et al, 2012 , 2015 ), in vitro electrophysiological studies of CMS patients revealed that ACh synthesis can be impaired directly (Engel et al, 1977 ; Engel and Lambert, 1987 ; Mora et al, 1987 ). Subsequently, over 40 CMS-related missense mutations have been identified in human 69-kDa ChAT protein, some of which have been partially characterized biochemically (Ohno et al, 2001 ; Byring et al, 2002 ; Kraner et al, 2003 ; Maselli et al, 2003 ; Schmidt et al, 2003 ; Barisic et al, 2005 ; Mallory et al, 2009 ; Yeung et al, 2009 ; Shen et al, 2011 ; Arredondo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%